2018
DOI: 10.2134/age2018.07.0017
|View full text |Cite
|
Sign up to set email alerts
|

External Inputs and Livestock for Organic Hill Land Farming Systems in Appalachia

Abstract: Hill land farmers, especially in Appalachia, are usually low external input grassland-based livestock producers with low output per hectare. Most of their land is unsuitable for annual crop production. Very little research has been published on organic crop production incorporated into livestock farming systems on hill land. Our objective was to compare the effects of four such systems on crop production and soil test results. The experiment had two fixed rotations, 4 and 7 yr, with two treatments at two level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As needed and appropriate, sheep assigned to these systems were allowed to rotationally graze the cultivated fields assigned to their system. Results from the cultivated fields have been published by Basweti et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As needed and appropriate, sheep assigned to these systems were allowed to rotationally graze the cultivated fields assigned to their system. Results from the cultivated fields have been published by Basweti et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…The research reported here was the permanent grassland part of a crop–livestock farming systems experiment initiated in 1999 with the start of the West Virginia University (WVU) Organic Crop–Livestock Research Farm, certified in 2003. Basweti et al (2018) published the results of that part of the experiment involving cultivated fields, annual crops, and ley. The permanent grassland part of the farming systems experiment, the results of which are reported here, provided the majority of the feed for the ewes and lambs included in that experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation